2009
DOI: 10.1519/jsc.0b013e3181bac69f
|View full text |Cite
|
Sign up to set email alerts
|

Can Shoulder Muscle Coordination During the Support Scale at Ring Height be Replicated During Training Exercises in Gymnastics?

Abstract: The support scale at ring height, the swallow, is a difficult strength element, usually performed in gymnastics. Coaches try to simulate the swallow position during training to strengthen muscles, specifically in the position used for competition. However, the real effect of this position's simulation on muscle force and coordination and consequently on the muscle activity has not been determined. The purpose of the study was to compare muscle activity and coordination during a swallow performed on the rings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“… 19 , 27 , 29 Shoulder injuries are well described in overhead athletes and swimmers, 6 , 22 , 23 , 25 , 28 , 31 but the current literature about gymnasts’ shoulders is scarce and concentrates on the biomechanics of gymnastic movements. 1 , 2 , 3 , 10 , 20 , 24…”
mentioning
confidence: 99%
“… 19 , 27 , 29 Shoulder injuries are well described in overhead athletes and swimmers, 6 , 22 , 23 , 25 , 28 , 31 but the current literature about gymnasts’ shoulders is scarce and concentrates on the biomechanics of gymnastic movements. 1 , 2 , 3 , 10 , 20 , 24…”
mentioning
confidence: 99%
“…This disparity may reflect the different types of gymnastic apparatus used by men (suspension and acrobatics apparatus such as the horizontal or the parallel bars) and the greater physical demands placed on the upper limbs and body in the men’s gymnastics maneuvers (eg, the iron cross position on the rings). 2 , 3 , 19…”
mentioning
confidence: 99%
“…Therefore, the isometric component of strength is important for gymnasts [38]. Bernasconi et al [39] showed that all top-level gymnasts perform the support scale at rings height. In addition, Bodray et al [40, 41] suggested that the circle performed on the pommel horse is a sequence of complex movements in which the amplitude, governed by a high isometric strength level, is the key component of the performance.…”
Section: Discussionmentioning
confidence: 99%